Leadership and Organizational Culture on Employee Engagement - Hasan, Halid; Nikmah, Farika; Resmita, Dini; Fajer, Nunung Aliyati (International Journal of Economics, Business and Innovation Research, 2025)
An organization faces the challenge of creating engaged employees. Several factors that can foster employee engagement are leadership and work culture. At the Indonesian Music Museum, employee engagement needs to be explored, given that it is a non-profit organization whose operational costs and funding are self-funded. This study employed qualitative methods, with the head and staff of the Indonesian Music Museum as the research subjects. Data collection techniques included participant observation, in-depth interviews, and documentation. The results provide an overview of the leadership style and organizational culture that influence employee engagement at the Indonesian Music Museum. The leadership style adopted by the head of the Indonesian Music Museum is democratic. This study explains that the two concepts of leadership and organizational culture complement each other. Effective leaders can shape and maintain a positive work culture, while a positive culture strengthens leadership effectiveness. The synergy between the two creates a work environment where employees feel motivated, valued, and have a sense of ownership, which is the core of employee engagement.